Studi Kajian Upaya Pemberian Obat Pencegah Masal Filariasis Terhadap Pengendalian Penyakit Infeksi Kecacingan - Anorital, Anorital; Dewi, Rita Marleta; Retnoningtyas, Kristina Palupi (Jurnal Biotek Medisiana Indonesia, 2016)
Abstract Filariasis and helminth infections are public health problems in Indonesia. Starting in 2005, the Ministry of Health launched filariasis elimination by implementing preventive mass drug administration (MDA) or âPOPMâ. At least asÂ  65% of the population in the district/city are given diethyl carbamazine citrate (DEC) and combined with albendazole. With the existence of this program, it is expectedÂ  filariasis can be eliminated and worm infections can be controled. This study aims to determine the constraints and problems encountered in the implementation of filariasis elimination and helminth infections control. The method applied is a review of scientific article, policyÂ  inventory, discussions with experts and practitioners, as well as confirmation data in the field. This study known 233 districts/cities in Indonesia were endemic filariasis with mf rate average of 3.61%, and the prevalence of helminth disease in 173 districts/cities with an average of 28.12%. Among the 233 districts/cities endemic filariasis, 104 districts/cities were also endemic helminth diseases; and only 135 regencies/citiesÂ  implemented MDA filariasis. Within the 135 districts/cities reported to implement MDA filariasis, only 16 districts/cities actually executed MDA with prevalence ofÂ  helminth infections above 30% (MDA helminth requirement). Recommendations is necessary to accelerate MDA filariasis in the district/city with endemic filariasis and also those with endemic helminth diseases above 30%.